The First Clinical Case of Intermediate Ex Vivo Normothermic Perfusion in Renal Transplantation. Issue 7 (9th May 2014) - Hosgood, S. A.; Nicholson, M. L.
<x xml:space="preserve">Abstract</x> A short period of ex vivo normothermic perfusion (EVNP) immediately before transplantation can revive the kidney and reduce the effects of cold ischemic (CI) injury. Herein, we report a clinical case of EVNP carried out at an intermediate period of the preservation interval. The kidney was retrieved from a 63‐year‐old extended criteria donor. After 10 h 29 min of CI the kidney underwent EVNP with 1 unit of compatible packed red blood cells mixed with a priming solution at 35.0°C while the recipient was being prepared for surgery. The mean renal blood flow was 93.6 mL/min/100 g and the kidney produced 60 mL of urine. Shortly after the start of surgery the first intended recipient became unfit for transplantation. After 60 min EVNP the kidney was flushed with cold preservation solution and re‐packed in ice. The second period of CI was 5 h and 21 min. The kidney was transplanted without any complications into a 54‐year‐old predialysis patient. The recipient had immediate graft function with serum creatinine levels falling from 315 to 105 µmol/L by day 7. This is the first report of an intermediate period of EVNP in clinical renal transplantation. This case demonstrates the feasibility and safety of the technique.